Inhibitory and excitatory neurotransmitter systems in depressed and healthy: A positron emission tomography and magnetic resonance spectroscopy study. (30th September 2021) - Persson, Jonas; Wall, Anders; Weis, Jan; Gingnell, Malin; Antoni, Gunnar; Lubberink, Mark; Bodén, Robert
Highlights: Medial prefrontal GABA and glutamate concentrations were assessed in 42 patients and 45 healthy controls. [11C]Flumazenil PET was used to assess GABA-A receptor availability in a subsample of 28 patients and 15 healthy controls. High levels of GABA in the prefrontal cortex was associated with low availability of GABA-A receptors in the same region, in depressed patients and healthy controls. Prior findings of reduced GABA and glutamate in depression was not replicated in this relatively large sample. Abstract: The Gamma-aminobutyric acid (GABA) and glutamate (Glu) neurotransmitter systems are implicated in depression. While previous studies found reduced GABA levels, and a tendency towards reduced Glu, using proton ( 1 H) magnetic resonance spectroscopy ( 1 H-MRS), little is known about GABAA receptor availability in depression. Here, the aim was to characterize GABA and Glu-levels in dorsal anterior cingulate cortex (dACC), whole-brain GABAA availability, and their relationship in patients with depression compared to healthy controls. Forty-two patients and 45 controls underwent 1 H-MRS using a MEGA-PRESS sequence to quantify dACC GABA+ and Glu (contrasted against creatine [Cr]). Immediately preceding the 1 H-MRS, a subsample of 28 patients and 15 controls underwent positron emission tomography (PET) with [ 11 C]Flumazenil to assess whole-brain GABAA receptor availability. There were no differences in dACC GABA+/Cr or Glu/Cr ratios between patients and controls. The same was true for whole-brain GABAA receptor availability. However, there was a significant negative relationship between GABA+/Cr ratio and receptor availability in ACC, in a whole-brain voxel-wise analysis across patients and controls, controlling for group or depressive symptoms. This relatively large study did not support the GABA-deficit hypothesis in depression, but shed light on GABA-system functioning, suggesting a balance between neurotransmitter concentration and receptor availability in dACC.